High throughput experimentation: a validation study for use in catalyst development - Luchters, Niels (Centre for Catalysis Research, 2016)
High throughput and combinatorial experimentation is becoming more and more used in catalysis research. The benefits of parallel experiments are not only limited to shorten the time - to - market, but also give opportunities to study the process in more depth by performing more experiments. The influence of a parameter, for example the amount of the active metal and/or promoter, to the process is better understood with a broader parameter space investigated. To study the parameter space, multiple experiments need to be performed. It is of paramount importance to understand the variability of the data between these experiments. This is not always defined, specifically when literature gives contradictory results, most often due to the time for duplicate experiments necessary. In this project the reproducibility and variance in high throughput catalyst preparation and testing was determined and the use of parallel experimentation was demonstrated within a catalyst development study. The high throughput equipment was used for catalyst development studies for fuel processing, the production of fuel cell - grade hydrogen from hydrocarbon fuels. Fuel processing consists of three catalytic reactions, namely reforming, water - gas shift and a CO clean - up through either selective methanation or preferential oxidation. Focus has been placed on the first two reactions, steam methane reforming (SMR) and medium temperature water - gas shift (WGS), using platinum group metals (PGM). All catalysts in this study (except for the commercial WGS catalyst) were prepared using automated synthesis robot (Chemspeed ISYNTH) and the activity testing was performed on the Avantium Flowrence. For both reactions two types of studies were performed, one - to - many and many - to - many; referring to one catalyst tested in many reactors or many prepared catalysts (same composition, different batches) tested in many reactors. For the WAGS one - to - many a commercial low temperature shift catalyst was selected and for SMR a single batch of Rh/Al 2 O 3 . The many - to - many experiments comprised of eight batches of prepared catalysts for both reactions. The WGS reaction was performed with 1 wt% Pt/Al 2 O 3 catalysts and for the reforming reaction batches of 0.5 wt% Rh/Al 2 O 3 was used. It was proven that in all these studies the experimental standard deviations in the data is 6%, from preparation to activity measurements. A study on the rhodium metal loading on alumina in the steam methane reforming catalyst was studied between 0.05 and 0.6 wt%. A 0.4 wt% Rh/Al 2 O 3 was found to have the highest activity per amount of rhodium. Lower Rh content would require decreased space velocity, whereas higher metal content does not increase the conversion due to larger crystals sizes. This study has been performed up to a metal loading of 0.6 wt% and it is recommended to follow - up with studying the range of 0.6 to ~2.5 wt% to investigate the optimal metal loading. It was shown that the use of automated experimentation (parallel preparation and evaluation under same condition) for catalyst development results in highly reproducible results with a relative standard deviation of ~6% activity. The high throughput equipment was demonstrate d to be a very powerful tool in catalyst research